A FUZZY PROBABILISTIC RELATIONAL DATABASE MODEL AND ALGEBRA - Nguyễn, Hòa (Journal of Computer Science and Cybernetics, 2016)
This paper introduces a complete extended relational data base model based on probability theory and fuzzy theory, called FPRDB, for representing and handling vague and uncertain information of objects in the real world applications. FPRDB is built by first extending probabilistic triples with fuzzy sets, associating the probability of such fuzzy sets for expressing and computing uncertain degree of imprecise information. Then, schemas, fuzzy probabilistic relations, fuzzy probabilistic functional dependencies and algebraic operations are defined coherently and consistently for FPRDB. A set of the properties of the probabilistic relational algebraic operations in FPRDB is also formulated and proven.